Performance, Intake, Feed Efficiency, and Carcass Characteristics of Young Nellore Heifers under Different Days on Feed in the Feedlot - Ferreira, Igor Machado [UNESP]; Oliveira, Karla Alves [UNESP]; Cidrini, Iorrano Andrade [UNESP]; de Abreu, Mateus José Inácio [UNESP]; Sousa, Luciana Melo [UNESP]; Batista, Luis Henrique Cursino [UNESP]; Homem, Bruno Grossi Costa; Prados, Laura Franco; Siqueira, Gustavo Rezende [UNESP]; Resende, Flávio Dutra de [UNESP] (MDPI, 2023)
Two studies evaluated the productive characteristics of young Nellore heifers receiving different days on feed (DOF) to determine the biological slaughter endpoint. In Experiment 1 (Exp. 1), fifty-one Nellore heifers [324 ± 19.3 kg of body weight (BW); 16 ± 1 months] were split into three DOF lengths (45, 75, or 105 days), while in Experiment 2 (Exp. 2), thirty-six Nellore heifers (362 ± 25.5 kg of BW; 18 ± 1 months of age) were split into three DOF lengths (45, 90, or 135 days). In both studies, all animals were distributed in complete randomized blocks according to initial BW and stratified via carcass ultrasound. The diet was supplied ad libitum, allowing 3% of refusals. The point at which the animals achieved 25% of ether extract of shrunk body weight (EESBW) was defined as the biological endpoint. Thus, relationships were made between some characteristics obtained in both studies. Positive linear relationships were found between backfat thickness (BFT) vs. EESBW (p < 0.001, r = 0.84) and BFT vs. body weight (p < 0.001, r = 0.77). Our results suggest that the biological slaughter endpoint for young Nellore heifers is 6.97 mm of backfat thickness or 402 kg shrunk body weight, corresponding to around 75 DOF.
Keywords: backfat thickness; carcass gain; days on feed; feed efficiency; Nellore heifers